Fabrication and mechanical properties of silicon carbide nanowires/epoxy resin composites - Nhuapeng W. (2014)
An experimental investigation was carried out to study the fabrication of silicon carbide nanowires (SiC NWs)/epoxy resin composites. This material could exhibit excellence mechanical properties for example, hardness, wear resistant and especially lightweight which may be used to replace metal parts in vehicles. The SiC NWs/epoxy resin composites were prepared by using the ultrasonic mixing and casting techniques. The physical and mechanical properties such as density, tensile strength, hardness and wear test of composite samples were examined. Furthermore, microstructures of samples were also investigated by scanning electron microscopy (SEM). It was found that the ultrasonic mixing could be used for fabricating high wear strength samples of SiC NWs/epoxy resin composites. © 2007 Elsevier B.V. All rights reserved.